Mobilizing high school students as climate-smart agriculture information providers in farming communities in the Philippines - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
From 2013 to 2016, the Youth Infomediary Campaign engaged 208 (out of 278) Technical Vocational (TecVoc) high schools in the Philippines providing research, training, and communication support focused on climate change in agriculture. The project trained 225 teachers that enrolled about 234,000 students in their classes. This has led to the integration by the Philippine Department of Education of CSA competencies in the curricula of 75 schools nationwide that now serve as CSA information hubs among TechVoc schools.